Long‐Term Outcome of Catheter Ablation in Atrial Fibrillation Patients with Coexistent Metabolic Syndrome and Obstructive Sleep Apnea: Impact of Repeat Procedures versus Lifestyle Changes. (4th July 2014) - MOHANTY, SANGHAMITRA; MOHANTY, PRASANT; DI BIASE, LUIGI; BAI, RONG; TRIVEDI, CHINTAN; SANTANGELI, PASQUALE; SANTORO, FRANCESCO; HONGO, RICHARD; HAO, STEVEN; BEHEIRY, SALWA; BURKHARDT, DAVID; GALLINGHOUSE, JOSEPH G.; et al.
Ablation Outcome in AF with Concurrent MS and OSA Introduction Metabolic syndrome (MS) and obstructive sleep apnea (OSA) are well‐known independent risk factors for atrial fibrillation (AF) recurrence. This study evaluated ablation outcome in AF patients with coexistent MS and OSA and influence of lifestyle modifications (LSM) on arrhythmia recurrence. Methods and Results We included 1, 257 AF patients undergoing first catheter ablation (30% paroxysmal AF). Patients having MS + OSA were classified into Group 1 (n = 126; 64 ± 8 years; 76% male). Group 2 (n = 1, 131; 62 ± 11 years; 72% male) included those with either MS (n = 431) or OSA (n = 112; no CPAP users) or neither of these comorbidities (n = 588). Patients experiencing recurrence after first procedure were divided into 2 subgroups; those having sporadic events (frequency < 2 months) remained on previously ineffective antiarrhythmic drugs (AAD) and aggressive LSM, while those with persistent arrhythmia (incessant or ≥2 months) underwent repeat ablation. After 34 ± 8 months of first procedure, 66 (52%) in Group 1 and 386 (34%) in Group 2 had recurrence (P < 0.001). Recurrence rate in only‐MS, only‐OSA, and without MS/OSA groups were 40%, 38%, and 29%, respectively. Patients with MS + OSA experienced substantially higher recurrence compared to those with lone MS or OSA (52% vs. 40% vs. 38%; P = 0.036). Of the 452 patients having recurrence, 250 underwent redo‐ablation and 194 remained on AAD and LSM. At 20 ± 6 months, 76% of the redo group remained arrhythmia‐free off AAD whereas 74% of the LSM group were free from recurrence (P = 0.71), 33% of which were off AAD. Conclusions MS and OSA have additive negative effect on arrhythmia recurrence following single procedure. Repeat ablation or compliant LSM increase freedom from recurrent AF.